Soil seed bank resilience in passively restored endangered Sand Fynbos following a century of pine plantations - Rebelo, Alanna J.; Holmes, Patricia M.; Rebelo, Anthony G.; Martin, Shaeleigh; Hattas, Safiyyah; Hall, Stuart; Esler, Karen J. (Plants, people, planet, 2025)
Societal Impact Statement Ecosystems are rapidly being transformed, pushing us towards irreversible losses and even extinctions. The Kunming‐Montreal Global Biodiversity Framework aims to curb biodiversity decline. An intriguing solution lies in seed banks—where plants store seeds in the soil. Restoration efforts can revive lost ecosystems by leveraging these seed banks. In the fynbos of South Africa, this study found that it is possible to bring back ecosystems that were lost as long ago as 100 years if conditions are right. Managers can achieve best results by applying a dry season prescribed burn following removal of the driver of degradation (e.g. pine plantations or invasions). Summary Soil‐stored seed banks are a critical evolutionary strategy for plants as they can stabilize population dynamics in response to environmental fluctuations such as droughts and natural disturbances such as fires, thus improving ecosystem resilience. This study aimed to assess resilience during the first restoration cycle of endangered Sand Fynbos following pine harvesting and a prescribed burn in South Africa. We compared above ground populations and soil‐stored seed bank composition and focused on six perennial fynbos focal species in five 1 m2 plots. All six species are obligate reseeders with soil‐stored seed banks but represent a variety of important fynbos growth forms and seed types. We found that native soil‐seed bank density following over a century of plantation forestry and 10 years after the first fynbos restoration burn was comparable to, or exceeded, densities measured in other fynbos studies, especially seed banks of alien‐invaded fynbos ecosystems. The early years following pine harvesting and a restoration burn likely provide a pest‐ and predator‐free window of opportunity in which plants may re‐establish and flourish. Our results show that even for old forestry plantation areas, ecological restoration to the historic vegetation community is feasible, where there is retained seed bank resilience, through a combination of passive and active restoration methods. Ecological restoration in cases where soil seed banks persist is therefore a viable and critically important method to attain 30% conservation of terrestrial land in ecosystems with less than 30% remaining, as part of the Kunming‐Montreal Global Biodiversity Framework. Ecosystems are rapidly being transformed, pushing us towards irreversible losses and even extinctions. The Kunming‐Montreal Global Biodiversity Framework aims to curb biodiversity decline. An intriguing solution lies in seed banks—where plants store seeds in the soil. Restoration efforts can revive lost ecosystems by leveraging these seed banks. In the fynbos of South Africa, this study found that it is possible to bring back ecosystems that were lost as long ago as 100 years if conditions are right. Managers can achieve best results by applying a dry season prescribed burn following removal of the driver of degradation (e.g. pine plantations or invasions).